Product formulation and product standardization of coco-mango bar - Sales, Maria Eliza Cruz; Dumelod, Benelyn Domingo (1995.)
The process for roasting cereals and boiling the syrup for coco-granola bar (Domingo, 1992) was adopted and adjusted to make coco-mango bar. Coco-mango bar is made from roasted coconut residue, mango bits and peanuts. Based on preliminary studies, the best syrup were at 180°C for 25 minutes and 108°C for 2 minutes, respectively. Using the mixture design, coco-mango bars with varying proportions of roasted coconut residue, mango and peanuts were prepared and subjected to sensory evaluation to determine the most acceptable proportion of ingredients. Results show that coco-mango bar with 57.5% roasted coconut residue, 27.5% mango and 15% peanut was the most acceptable. It was given a rating of 7.6 which corresponded to "like moderately" to "like very much". The most acceptable proportion of ingredients for coco-mango bar was used for the bench scale production. Samples used for moisture, fat, protein, total available carbohydrate, total dietary fiber and ash content determinations were taken from this production. Cost analysis of coco-mango bar (per bar) was also done. Results of the analyses showed that coco-mango bar contains 2.92% moisture, 14.94% fat, 3.31% protein, 64.17%total available carbohydrate, 13.81% total dietary fiber and 0.85% ash. One serving of 35±5 g costs P4.38 and provides approximately 7 grams of dietary fiber and 161 calories.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut products; Mango